OBSTACLES IN IMPLEMENTING MERDEKA CURRICULUM IN HINDU EDUCATION: A CIPP STUDY IN DENPASAR SCHOOLS - Ni Made Muliani; Ida Ayu Gde Yadnyawati; Ni Made Indiani (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to evaluate the obstacles faced in the implementation of the Merdeka Curriculum in the learning of Hindu Religious Education and character education for class X students in State Senior High Schools throughout Denpasar City, reviewed from the dimensions of context, input, process, and product. This study uses an evaluative approach with the CIPP model. Data were collected through observation, interviews, and questionnaires, then analyzed descriptively qualitatively. For the results of the study in the form of internal and external obstacles faced by students in implementing the Merdeka curriculum in Hindu religious and character education, it shows that more students do not experience obstacles in the three research locations. The conclusion in this study is that the implementation of the Merdeka curriculum in Hindu religious and moral learning both in SMA N 1, SMA N 4 and SMA N 7 Denpasar is effective and only a few students experience obstacles. The findings are factual and theoretical findings.